2010
DOI: 10.3109/14767050903410664
|View full text |Cite
|
Sign up to set email alerts
|

Fetal death: A condition with a dissociation in the concentrations of soluble vascular endothelial growth factor receptor-2 between the maternal and fetal compartments

Abstract: OBJECTIVE An anti-angiogenic state has been implicated in the pathophysiology of preeclampsia, fetal growth restriction and fetal death. Vascular endothelial growth factor (VEGF), an indispensible angiogenic factor for embryonic and placental development exerts its angiogenic properties through the VEGF receptor (VEGFR)-2. A soluble form of this protein (sVEGFR-2) has been recently detected in maternal blood. The aim of this study was to determine if fetal death was associated with changes in the concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…We have demonstrated that an imbalance of angiogenic/anti-angiogenic factor concentrations is not a unique characteristic of patients with PE since this perturbation can occur in isolated fetal growth restriction with abnormal uterine artery Doppler velocimetry [96], unexplained fetal death [160163], twin-to-twin transfusion syndrome [164] and viral-induced hydrops fetalis [165,166] or Ballantynes syndrome [167]. Moreover, a subset of patients with spontaneous preterm labor with intact membranes also had an abnormal angiogenic/anti-angiogenic profile in maternal circulation prior to the diagnosis of preterm labor/delivery [168].…”
Section: Discussionmentioning
confidence: 99%
“…We have demonstrated that an imbalance of angiogenic/anti-angiogenic factor concentrations is not a unique characteristic of patients with PE since this perturbation can occur in isolated fetal growth restriction with abnormal uterine artery Doppler velocimetry [96], unexplained fetal death [160163], twin-to-twin transfusion syndrome [164] and viral-induced hydrops fetalis [165,166] or Ballantynes syndrome [167]. Moreover, a subset of patients with spontaneous preterm labor with intact membranes also had an abnormal angiogenic/anti-angiogenic profile in maternal circulation prior to the diagnosis of preterm labor/delivery [168].…”
Section: Discussionmentioning
confidence: 99%
“…In early pregnancy, a severe anti-angiogenic state is likely to lead to fetal death. 98100 Why continue to invest maternal resources when there is not enough of an angiogenic drive to maintain the placenta and fetus? In milder cases of uteroplacental ischemia, isolated small-for-gestational-age fetus (SGA), SGA plus hypertension or late preterm labor could provide a solution.…”
Section: Vascular Pathology As a Mechanism Of Disease In Obstetricsmentioning
confidence: 99%
“…An imbalance of angiogenic/anti-angiogenic factors has been implicated in the pathophysiology of PE, 6788 pregnancies with SGA neonates, 89–92 stillbirth, 9395 and other obstetrical complications. 96102 Changes in the concentrations of the angiogenic factor, placental growth factor (PlGF), and anti-angiogenic factors, soluble vascular endothelial growth factor receptor (sVEGFR)-1 [also known as soluble fms-like tyrosine kinase-1 (sflt-1)] and soluble endoglin (sEng) in maternal circulation, precede the clinical diagnosis of PE, 103109 SGA 90,91 and stillbirth.…”
Section: Introductionmentioning
confidence: 99%